A composite modified high temperature resistant friction material and preparation method thereof
By adding Cr and La2O3 to the copper-ferroalloy matrix for solid solution and dispersion strengthening, and combining the composite reinforced phase and lubricated phase, the wear problem of copper-ferroalloy friction sheets under high temperature conditions is solved, and the effect of low friction coefficient and low wear rate is achieved, and the service life is extended.
Patent Information
- Application Number
- CN202410707452.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-06-03
AI Technical Summary
The existing copper-ferroalloy friction plates have wear of abrasive particles and peeling layer under high temperature conditions, resulting in a large number of furrows and peeling on the friction surface, rapidly increasing the wear rate and decreasing service life.
By adding Cr and La2O3 to the copper-ferroalloy matrix for solid solution and dispersion strengthening, and combining the composite reinforced phase (Ti3SiC2+TiAl) and the composite lubricated phase (Ag2MoO4+Ag), their ratio is adjusted to achieve friction performance optimization at high temperatures.
The low friction coefficient and low wear rate of copper and ferroalloy friction sheets under high temperature conditions are achieved, which extends the service life and improves the structural uniformity, hardness and strength of the material.
Smart Images

Figure BDA0004873046090000111 
Figure BDA0004873046090000121 
Figure BDA0004873046090000122
Abstract
Description
Technical Field
[0001] The invention relates to a composite modified high temperature resistant friction material and a preparation method thereof, in particular to a composite modified high temperature resistant friction material by silver molybdate and MAX and a preparation method thereof, belonging to the technical field of friction materials. Background Art
[0002] Copper-iron alloy has high hardness, strength and wear resistance, and is widely used in high-speed rail brake pads and heavy-duty vehicle dry brake friction pads. However, copper-iron alloy friction pads will experience strong abrasive wear and delamination wear under high-temperature conditions, resulting in a large number of furrows and peeling on the friction surface, a rapid increase in wear rate, and a decrease in service life. In order to achieve higher reliability and service life for copper-iron alloy friction pads, their thickness and weight are usually large, which has an adverse effect on vehicle efficiency and space utilization. Therefore, how to improve the tribological properties of copper-iron alloys under high-temperature oil-free conditions is a problem worthy of attention.
[0003] Chinese patent CN106086585B reduces the friction coefficient and wear rate by adding graphite and Al2O3 to the copper-iron alloy matrix, but if excellent friction performance is to be maintained under high temperature conditions, the required graphite and Al2O3 content is relatively high, which will have an adverse effect on the material's organizational uniformity, mechanical strength and wear resistance. Chinese patents CN112011748B and CN110284083B improve the material's heat resistance and service life by adding carbon fiber to the copper alloy, but as the carbon fiber content increases, the initiation and expansion of cracks inside the material intensify, which will have an adverse effect on the mechanical properties. Chinese patent CN104384503B prepares a copper-iron-based powder metallurgy anti-friction material. The sample needs to be immersed in oil, and the performance fluctuates greatly when used on dry brake friction pads for a long time. Chinese patent CN102703161B improves the self-lubricating properties of the material by adding an appropriate amount of Ti3SiC2 to the copper matrix. The matrix is pure copper, which has low strength and hardness and is difficult to use in heavy load and strong impact conditions. Chinese patent CN103184385A combines a variety of M n+1 XA n The compound is added to the brake pad material as a reinforcing phase, but it lacks the coordination with the lubricating phase, resulting in a high friction coefficient and wear rate of the material. n+1 XA nThe addition amount of the compound reaches 15% to 35%, and its high content is likely to lead to a decrease in the toughness and strength of the matrix. The above research results show that the strengthening effect of the traditional strengthening phase on the copper-iron alloy matrix is limited, and when the content is high, it will have an adverse effect on the uniformity of the material's organization and mechanical strength; at the same time, the modification effect of a single strengthening phase or lubricating phase is limited. Therefore, it is necessary to study new composite strengthening phase and lubricating phase formulas and material preparation methods to further improve the friction and wear properties of copper-iron alloys at high temperatures. Summary of the invention
[0004] In order to overcome the defects of the prior art, one of the purposes of the present invention is to provide a composite modified high temperature resistant friction material. The high temperature resistant friction material strengthens the copper-iron alloy matrix by precisely controlling the addition amount of Cr and La2O3, and adds a composite strengthening phase (Ti3SiC2+TiAl) so that the copper-iron alloy has both good mechanical properties and anti-wear properties, and also provides a composite lubricating phase (Ag2MoO4+Ag), and adjusts its ratio so that the high temperature lubrication performance of Ag2MoO4 and the medium and low temperature lubrication performance of Ag are superimposed on each other; by simultaneously adding the composite strengthening phase (Ti3SiC2+TiAl) and the composite lubricating phase (Ag2MoO4+Ag), and adjusting their ratio so that the weakening of adhesive wear effect of (Ti3SiC2+TiAl) and the weakening of abrasive wear effect of (Ag2MoO4+Ag) are coupled to each other, the friction coefficient and wear rate are reduced.
[0005] A second object of the present invention is to provide a method for preparing a composite modified high temperature resistant friction material.
[0006] In order to achieve the purpose of the present invention, the following technical solutions are provided.
[0007] A composite modified high temperature resistant friction material, taking the total mass of the raw material of the high temperature resistant friction material as 100%, wherein the components and their mass fractions are as follows:
[0008] Copper-iron alloy matrix 70.0%~90.0%,
[0009] Composite lubricating phase 5.0%~15.0%,
[0010] Composite strengthening phase 5.0%~15.0%.
[0011] The raw material of the copper-iron alloy matrix is a mixed powder composed of copper (Cu), aluminum (Al), nickel (Ni), iron (Fe), chromium (Cr) and lanthanum trioxide (La2O3). Taking the total mass of the raw material of the high-temperature friction material as 100%, the raw materials of the copper-iron alloy matrix and their mass fractions are as follows:
[0012] Copper (Cu) 30.0% ~ 45.0%, aluminum (Al) 3.0% ~ 9.0%, nickel (Ni) 3.0% ~ 13.0%, iron (Fe) 19.5% ~ 36.0%, chromium (Cr) 0.5% ~ 1.0%, lanthanum trioxide (La2O3) 0.5% ~ 1.0%.
[0013] The composite lubricating phase is a mixed powder composed of silver molybdate (Ag2MoO4) and silver (Ag). Taking the total mass of the composite lubricating phase raw material as 100%, the components and their mass fractions are: Ag2MoO4 30.0%-70.0%, Ag 30.0%-70.0%.
[0014] The composite lubricating phase is a mixed powder formed by mixing Ag2MoO4 and Ag by wet ball milling; wherein Ag2MoO4 is a powder with a particle size greater than or equal to 200 mesh, and Ag is a powder with a particle size greater than or equal to 200 mesh.
[0015] Preferably, the composite lubricating phase is prepared according to the following method:
[0016] Ag2MoO4 powder and Ag powder are wet-milled under inert gas protection, with ethanol as the ball-to-material ratio of 3:1-4:1, a rotation speed of 250 r / min-350 r / min, and a ball-milling time of 8 h-12 h. The milling is stopped every 5 min-10 min, and the milling is continued after 2 min-3 min of stopping to obtain a mixed powder, which is the composite lubricating phase.
[0017] The composite strengthening phase is a mixed powder composed of titanium silicon carbon compound (Ti3SiC2) and titanium aluminum compound (TiAl). Taking the total mass of the composite strengthening phase raw material as 100%, the components and their mass fractions are: Ti3SiC2 60.0% to 80.0%, TiAl 20.0% to 40.0%.
[0018] The composite reinforcement phase is a mixed powder formed by mixing Ti3SiC2 and TiAl by wet ball milling; wherein Ti3SiC2 is a powder with a particle size greater than or equal to 200 meshes, and TiAl is a powder with a particle size greater than or equal to 200 meshes.
[0019] Preferably, the composite reinforcement phase is prepared according to the following method:
[0020] Ti3SiC2 powder and TiAl powder are wet-milled under inert gas protection, with ethanol as the ball-to-material ratio of 3:1-4:1, a rotation speed of 250 r / min-350 r / min, and a ball-milling time of 8 h-12 h. The milling is stopped every 5 min-10 min, and the milling is continued after 2 min-3 min of stopping to obtain a mixed powder, which is the composite reinforcement phase.
[0021] A method for preparing the composite modified high temperature resistant friction material of the present invention comprises: mixing a copper-iron alloy matrix raw material, a composite lubricating phase and a composite strengthening phase by mechanical ball milling to obtain a mixed powder, and then hot pressing and sintering the mixed powder to prepare the material.
[0022] Specifically, the mechanical ball milling mixing steps are as follows:
[0023] The copper-iron alloy matrix raw material, the composite lubricating phase and the composite strengthening phase are dry-milled in an inert gas atmosphere, with a ball-to-material ratio of 1:1 to 2:1, a rotation speed of 100 r / min to 150 r / min, a ball milling time of 8 h to 10 h, and the ball milling is stopped every 10 min to 15 min, and the ball milling is continued after stopping for 1 min to 2 min; a mixed powder is prepared; the grinding jar and the grinding balls used in the ball milling are made of tungsten carbide cemented carbide.
[0024] Specifically, the hot pressing sintering steps are as follows:
[0025] The mixed powder prepared by ball milling was placed into a mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 100℃ / min~150℃ / min, the sintering temperature is 850℃~900℃, the applied pressure is 35MPa~40MPa, the constant temperature and pressure are maintained for 5min~10min to end the hot pressing sintering, and the furnace is cooled to room temperature to prepare a composite modified high temperature resistant friction material;
[0026] The mold used in hot pressing sintering is usually a graphite mold.
[0027] In the present invention, the ball-to-material ratio refers to the ratio of the weight of the grinding body (grinding balls) in the ball mill to the weight of the material.
[0028] Beneficial Effects
[0029] (1) The present invention provides a composite modified high temperature resistant friction material, wherein the high temperature resistant friction material generates a solid solution strengthening effect by adding Cr element to the copper-iron alloy matrix and generates a dispersion strengthening effect by adding La2O3 to be dispersed in the matrix. Compared with the existing matrix strengthening technology, the present invention combines the solid solution strengthening effect of Cr element with the dispersion strengthening effect of La2O3 by accurately controlling the relative content of Cr and La2O3, so that the high temperature resistant friction material has excellent structural uniformity, hardness and strength.
[0030] (2) The present invention provides a composite modified high temperature resistant friction material, which adds a composite strengthening phase (Ti3SiC2+TiAl) to a copper-iron alloy matrix, reduces the plowing and peeling effects of the contact surface through a pinning mechanism without affecting the strength of the matrix, and improves the wear resistance and service life of the matrix under high temperature dry friction conditions. The amount of Ti3SiC2 and TiAl in the composite strengthening phase will have a significant impact on the comprehensive performance of the high temperature resistant friction material. If there is too much Ti3SiC2 and too little TiAl, the mechanical properties of the high temperature resistant friction material will decrease due to decreased interface wettability and excessive impurities; if there is too little Ti3SiC2 and too much TiAl, it is difficult to effectively improve the wear resistance of the high temperature resistant friction material. Compared with copper-iron alloys that add commonly used strengthening phases such as Al2O3, the present invention achieves a balance between mechanical properties and wear resistance by accurately controlling the content of Ti3SiC2 and TiAl.
[0031] (3) The present invention provides a composite modified high temperature resistant friction material. The high temperature resistant friction material can form a hard, stable separation film with low shear force on the friction surface by adding a composite lubricating phase (Ag2MoO4+Ag) to the copper-iron alloy matrix, thereby improving the friction reduction performance of the matrix under extreme braking high temperature conditions. The content of Ag2MoO4 and Ag will have a significant impact on the performance of the high temperature resistant friction material. If there is too much Ag2MoO4 and too little Ag, the strength and wear resistance of the high temperature resistant friction material will decrease due to the decrease in internal bonding force and excessive grain boundary impurities; if there is too little Ag2MoO4 and too much Ag, it is difficult to effectively improve the lubrication performance of the high temperature resistant friction material under high temperature conditions. Compared with copper-iron alloys with commonly used lubricating phases such as graphite, the present invention accurately controls the content of Ag2MoO4 and Ag, so that the high temperature lubrication performance of Ag2MoO4 and the medium and low temperature lubrication performance of Ag are superimposed on each other, so that the high temperature resistant friction material has a lower and more stable friction coefficient under high temperature conditions.
[0032] (4) The present invention provides a composite modified high temperature resistant friction material, wherein the high temperature resistant friction material improves the anti-friction and anti-wear performance by simultaneously adding a composite lubricating phase (Ag2MoO4+Ag) and a composite reinforcing phase (Ti3SiC2+TiAl) to a copper-iron alloy matrix. Compared with materials containing only one added phase, the present invention achieves the mutual coupling of the composite reinforcing phase's weakening adhesive wear effect and the composite lubricating phase's weakening abrasive wear effect under high temperature conditions by accurately controlling the content of the composite reinforcing phase and the composite lubricating phase, so that the high temperature resistant friction material has both a lower friction coefficient and a wear rate.
[0033] (5) The present invention provides a composite modified high temperature resistant friction material, which has a high hardness of 216HV to 222HV, and high strength, with a compressive strength of 901MPa to 1099MPa and a bending strength of 726MPa to 913MPa, and has a low wear rate and friction coefficient under high temperature and room temperature conditions. At the same time, the material has low cost, high economic benefits, and a wide range of applications. It is suitable for dry friction working components such as high-speed rail brake pads and heavy-duty vehicle dry brake friction pads, and has a relatively broad application prospect.
[0034] (6) The present invention provides a method for preparing a composite modified high temperature resistant friction material, wherein the composite lubricating phase (Ag2MoO4+Ag) is prepared by high energy ball milling of Ag2MoO4 powder and Ag powder, and the mass ratio of Ag2MoO4 powder and Ag powder and the high energy ball milling process are obtained through multiple experiments, which can improve the uniformity and surface chemical energy of the composite lubricating phase, making it easier to closely bond with the copper-iron alloy interface and evenly distribute during hot pressing sintering;
[0035] The composite strengthening phase (Ti3SiC2+TiAl) used is prepared by high-energy ball milling of Ti3SiC2 powder and TiAl powder. The mass ratio of Ti3SiC2 powder and TiAl powder and the high-energy ball milling process are obtained through multiple experiments, which can improve the uniformity and surface chemical energy of the composite strengthening phase, making it easier to closely bond with the copper-iron alloy interface and evenly distribute during hot pressing sintering.
[0036] (7) The present invention provides a method for preparing a composite modified high temperature resistant friction material, wherein the copper-iron alloy matrix raw material, the composite lubricating phase and the composite reinforcing phase are ball milled under the protection of an inert gas, the obtained mixed powder is placed in a sintering furnace for hot pressing and sintering, and the mixed powder is cooled in the furnace after sintering. Compared with the existing preparation technology, the preparation process of the present invention is obtained through multiple experiments, which can improve the uniformity and strength of the material on the one hand, and improve the density and hardness on the other hand. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with specific embodiments, but is not intended to limit the present invention.
[0038] A composite modified high temperature resistant friction material, taking the total mass of the raw material of the high temperature resistant friction material as 100%, wherein the components and their mass fractions are as follows:
[0039] Copper-iron alloy matrix 70.0%~90.0%,
[0040] Composite lubricating phase 5.0%~15.0%,
[0041] Composite strengthening phase 5.0%~15.0%.
[0042] The raw material of the copper-iron alloy matrix is a mixed powder composed of copper (Cu), aluminum (Al), nickel (Ni), iron (Fe), chromium (Cr) and lanthanum trioxide (La2O3). Taking the total mass of the raw material of the high-temperature friction material as 100%, the mass fractions of the components of the raw material of the copper-iron alloy matrix are as follows:
[0043] Copper (Cu) 30.0% ~ 45.0%, aluminum (Al) 3.0% ~ 9.0%, nickel (Ni) 3.0% ~ 13.0%, iron (Fe) 19.5% ~ 36.0%, chromium (Cr) 0.5% ~ 1.0%, lanthanum trioxide (La2O3) 0.5% ~ 1.0%.
[0044] The composite lubricating phase is a mixed powder composed of silver molybdate (Ag2MoO4) and silver (Ag). Taking the total mass of the composite lubricating phase raw material as 100%, the components and their mass fractions are: Ag2MoO4 30.0%-70.0%, Ag 30.0%-70.0%.
[0045] The composite lubricating phase is a mixed powder formed by mixing Ag2MoO4 and Ag by wet ball milling; wherein Ag2MoO4 is a powder with a particle size greater than or equal to 200 mesh, and Ag is a powder with a particle size greater than or equal to 200 mesh.
[0046] Preferably, the composite lubricating phase is prepared according to the following method:
[0047] Ag2MoO4 powder and Ag powder are wet-milled under inert gas protection, with ethanol as the ball-to-material ratio of 3:1-4:1, a rotation speed of 250 r / min-350 r / min, and a ball-milling time of 8 h-12 h. The milling is stopped every 5 min-10 min, and the milling is continued after 2 min-3 min of stopping to obtain a mixed powder, which is the composite lubricating phase.
[0048] The composite strengthening phase is a mixed powder composed of titanium silicon carbon compound (Ti3SiC2) and titanium aluminum compound (TiAl). Taking the total mass of the composite strengthening phase raw material as 100%, the components and their mass fractions are: Ti3SiC2 60.0% to 80.0%, TiAl20.0% to 40.0%.
[0049] The composite reinforcement phase is a mixed powder formed by mixing Ti3SiC2 and TiAl by wet ball milling; wherein Ti3SiC2 is a powder with a particle size greater than or equal to 200 meshes, and TiAl is a powder with a particle size greater than or equal to 200 meshes.
[0050] Preferably, the composite reinforcement phase is prepared according to the following method:
[0051] Ti3SiC2 powder and TiAl powder are wet-milled under inert gas protection, with ethanol as the ball-to-material ratio of 3:1-4:1, a rotation speed of 250 r / min-350 r / min, and a ball-milling time of 8 h-12 h. The milling is stopped every 5 min-10 min, and the milling is continued after 2 min-3 min of stopping to obtain a mixed powder, which is the composite reinforcement phase.
[0052] A method for preparing the composite modified high temperature resistant friction material of the present invention comprises: mixing a copper-iron alloy matrix raw material, a composite lubricating phase and a composite strengthening phase by mechanical ball milling to obtain a mixed powder, and then hot pressing and sintering the mixed powder to prepare the material.
[0053] Specifically, the mechanical ball milling mixing steps are as follows:
[0054] The copper-iron alloy matrix raw material, the composite lubricating phase and the composite strengthening phase are dry-milled in an inert gas atmosphere, with a ball-to-material ratio of 1:1 to 2:1, a rotation speed of 100 r / min to 150 r / min, a ball milling time of 8 h to 10 h, and the ball milling is stopped every 10 min to 15 min, and the ball milling is continued after stopping for 1 min to 2 min; a mixed powder is prepared; the grinding jar and the grinding balls used in the ball milling are made of tungsten carbide cemented carbide.
[0055] Specifically, the hot pressing sintering steps are as follows:
[0056] The mixed powder prepared by ball milling was placed into a mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 100℃ / min~150℃ / min, the sintering temperature is 850℃~900℃, the applied pressure is 35MPa~40MPa, the constant temperature and pressure are maintained for 5min~10min to end the hot pressing sintering, and the furnace is cooled to room temperature to prepare a composite modified high temperature resistant friction material;
[0057] The mold used for hot pressing sintering is a graphite mold.
[0058] The ball-to-material ratio refers to the ratio of the weight of the grinding balls to the weight of the material in the ball mill.
[0059] Example 1
[0060] A method for preparing a composite modified high temperature resistant friction material, the method steps are as follows:
[0061] Weigh 30.0g of Cu, 9.0g of Al, 13.0g of Ni, 36.0g of Fe, 1.0g of Cr, 1.0g of La2O3, 5.0g of composite lubricating phase (Ag2MoO4+Ag) mixed powder and 5.0g of composite strengthening phase (Ti3SiC2+TiAl) mixed powder, and mix them by dry ball milling under argon atmosphere. The materials of the grinding jar and grinding balls are both tungsten carbide cemented carbide, the ball-to-material ratio is 1:1, the rotation speed is 100r / min, the ball milling time is 8h, stop every 10min, and continue ball milling after stopping for 1min to prepare a mixed powder.
[0062] The mixed powder was placed in a graphite mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 100℃ / min, the sintering temperature is 850℃, the applied pressure is 35MPa, the constant temperature and pressure are maintained for 5min, the hot pressing sintering is terminated, and the material is cooled to room temperature with the furnace to obtain a composite modified high temperature resistant friction material.
[0063] Wherein, the composite lubricating phase is prepared according to the following method:
[0064] Weigh 30.0 g of Ag2MoO4 powder and 70.0 g of Ag powder, and perform wet ball milling under argon atmosphere. Before ball milling, add 1 ml of anhydrous ethanol as a ball milling medium, the ball-to-material ratio is 3:1, the rotation speed is 250 r / min, the ball milling time is 8 h, stop every 10 min, and continue ball milling after stopping for 2 min; obtain the composite lubricating phase; wherein, the particle size of Ag2MoO4 powder and Ag powder are both 200 mesh.
[0065] The composite reinforcement phase is prepared by the following method:
[0066] Weigh 60.0g of Ti3SiC2 powder and 40.0g of TiAl powder, and perform wet ball milling under argon atmosphere. Before ball milling, add 1ml of anhydrous ethanol as a ball milling medium, the ball-to-material ratio is 3:1, the rotation speed is 250r / min, the ball milling time is 8h, stop every 10min, and continue ball milling after stopping for 2min to obtain the composite strengthening phase; wherein, the particle size of Ti3SiC2 powder and TiAl powder are both 200 mesh.
[0067] The performance test of a composite modified high temperature resistant friction material prepared in this embodiment is as follows:
[0068] (1) The hardness of the test piece is 222HV using a Vickers hardness tester.
[0069] (2) The mechanical properties were tested using a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1 mm / min. The test results showed that the compressive strength of the high temperature resistant friction material was 1049 MPa and the bending strength was 863 MPa.
[0070] (3) The high-temperature tribological properties were evaluated using a HT-1000 high-temperature friction and wear tester. The dual ball was a 316 stainless steel ball, the load was 5N, the sliding speed was 0.1m / s, the friction radius was 5mm, the running time was 30min, and the test temperatures were 25℃ and 600℃, respectively. The test showed that the average friction coefficient of the high-temperature friction material at room temperature was 0.30, and the average wear rate was 0.8×10 -4 mm 3 / N·m; the average friction coefficient at 600℃ is 0.51, and the average wear rate is 3.5×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0071] The above performance test results indicate that the composite modified high temperature resistant friction material prepared in this embodiment has a low and stable friction coefficient and wear rate under high temperature conditions, and has good friction reduction and anti-wear properties.
[0072] Example 2
[0073] A method for preparing a composite modified high temperature resistant friction material, the method steps are as follows:
[0074] Weigh 45.0g of Cu, 6.0g of Al, 10.0g of Ni, 20.0g of Fe, 0.5g of Cr, 0.5g of La2O3, 9.0g of composite lubricating phase (Ag2MoO4+Ag) mixed powder and 9.0g of composite strengthening phase (Ti3SiC2+TiAl) mixed powder, and mix them by dry ball milling under argon atmosphere. The materials of the grinding jar and grinding balls are both tungsten carbide cemented carbide, the ball-to-material ratio is 1.5:1, the rotation speed is 130r / min, the ball milling time is 9h, stop every 12min, and continue ball milling after stopping for 1min to prepare a mixed powder.
[0075] The mixed powder was placed in a graphite mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 130℃ / min, the sintering temperature is 875℃, the applied pressure is 38MPa, the constant temperature and pressure are maintained for 7min, the hot pressing sintering is terminated, and the furnace is cooled to room temperature to obtain a composite modified high temperature resistant friction material.
[0076] Wherein, the composite lubricating phase is prepared according to the following method:
[0077] Weigh 50.0 g of Ag2MoO4 powder and 50.0 g of Ag powder, and perform wet ball milling under argon atmosphere. Before ball milling, add 2 ml of anhydrous ethanol as a ball milling medium, the ball-to-material ratio is 3.5:1, the rotation speed is 300 r / min, the ball milling time is 9 h, stop every 7 min, and continue ball milling after stopping for 2 min to obtain the composite lubricating phase; wherein, the particle size of Ag2MoO4 powder and Ag powder are both 200 mesh.
[0078] The composite reinforcement phase is prepared by the following method:
[0079] Weigh 70.0g of Ti3SiC2 powder and 30.0g of TiAl powder, and perform wet ball milling under argon atmosphere. Add 2ml of anhydrous ethanol as ball milling medium before ball milling. The ball-to-material ratio is 3.5:1, the rotation speed is 300r / min, the ball milling time is 10h, stop every 7min, and continue ball milling after stopping for 2min to obtain the composite strengthening phase; wherein, the particle size of Ti3SiC2 powder and TiAl powder is 200 mesh.
[0080] The performance test of a composite modified high temperature resistant friction material prepared in this embodiment is as follows:
[0081] (1) The hardness is 216HV when tested by Vickers hardness tester;
[0082] (2) Mechanical properties were tested using a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1 mm / min. The test results showed that the compressive strength of the high temperature resistant friction material was 988 MPa and the bending strength was 802 MPa;
[0083] (3) The high-temperature tribological properties were evaluated using a HT-1000 high-temperature friction and wear tester. The dual ball was a 316 stainless steel ball, the load was 5N, the sliding speed was 0.2m / s, the friction radius was 5mm, the running time was 30min, and the test temperatures were 25℃ and 600℃, respectively. The test showed that the average friction coefficient of the high-temperature friction material at room temperature was 0.25, and the average wear rate was 0.6×10 -4 mm 3 / N·m; the average friction coefficient at 600℃ is 0.45, and the average wear rate is 3.2×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0084] The above performance test results indicate that the composite modified high temperature resistant friction material prepared in this embodiment has a low and stable friction coefficient and wear rate under high temperature conditions, and has good friction reduction and anti-wear properties.
[0085] Example 3
[0086] A method for preparing a composite modified high temperature resistant friction material, the method steps are as follows:
[0087] Weigh 35.0g of Cu, 5.0g of Al, 6.0g of Ni, 22.0g of Fe, 1.0g of Cr, 1.0g of La2O3, 15.0g of composite lubricating phase (Ag2MoO4+Ag) mixed powder and 15.0g of composite strengthening phase (Ti3SiC2+TiAl) mixed powder, and mix them by dry ball milling under argon atmosphere. The materials of the grinding jar and grinding balls are both tungsten carbide cemented carbide, the ball-to-material ratio is 2:1, the rotation speed is 150r / min, the ball milling time is 10h, stop every 15min, and continue ball milling after stopping for 2min to prepare a mixed powder.
[0088] The mixed powder was placed in a graphite mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 150℃ / min, the sintering temperature is 900℃, the applied pressure is 40MPa, the constant temperature and pressure are maintained for 10min, the hot pressing sintering is terminated, and the material is cooled to room temperature with the furnace to obtain a composite modified high temperature resistant friction material.
[0089] Wherein, the composite lubricating phase is prepared according to the following method:
[0090] Weigh 70.0 g of Ag2MoO4 powder and 30.0 g of Ag powder, and perform wet ball milling under argon atmosphere. Before ball milling, add 3 ml of anhydrous ethanol as a ball milling medium, the ball-to-material ratio is 4:1, the rotation speed is 350 r / min, the ball milling time is 12 h, stop every 5 min, and continue ball milling after stopping for 3 min to obtain the composite lubricating phase; wherein, the particle size of Ag2MoO4 powder and Ag powder are both 200 mesh.
[0091] The composite reinforcement phase is prepared by the following method:
[0092] Weigh 80.0g of Ti3SiC2 powder and 20.0g of TiAl powder, and perform wet ball milling under argon atmosphere. Before ball milling, add 3ml of anhydrous ethanol as ball milling medium, the ball-to-material ratio is 4:1, the rotation speed is 320r / min, the ball milling time is 12h, stop every 5min, and continue ball milling after stopping for 3min to obtain the composite strengthening phase; wherein, the particle size of Ti3SiC2 powder and TiAl powder are both 200 mesh.
[0093] The performance test of a composite modified high temperature resistant friction material prepared in this embodiment is as follows:
[0094] (1) The hardness is 220HV when tested by Vickers hardness tester;
[0095] (2) Mechanical properties were tested using a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1 mm / min. The test results showed that the compressive strength of the high temperature resistant friction material was 901 MPa and the bending strength was 726 MPa;
[0096] (3) The high-temperature tribological properties were evaluated using a HT-1000 high-temperature friction and wear tester. The dual ball was a 316 stainless steel ball, the load was 5N, the sliding speed was 0.2m / s, the friction radius was 5mm, the running time was 30min, and the test temperatures were 25℃ and 600℃, respectively. The test showed that the average friction coefficient of the high-temperature friction material at room temperature was 0.21, and the average wear rate was 0.5×10 -4 mm 3 / N·m; the average friction coefficient at 600℃ is 0.40, and the average wear rate is 2.9×10 -4 mm 3 / N·m, with good anti-friction and anti-wear properties.
[0097] The above performance test results indicate that the composite modified high temperature resistant friction material prepared in this embodiment has a low and stable friction coefficient and wear rate under high temperature conditions, and has good friction reduction and anti-wear properties.
[0098] Comparative Example 1
[0099] Relative to Example 1, Comparative Example 1 provides a friction-resistant material, wherein no Cr and La2O3 are added to the copper-iron alloy matrix raw material, and the specific composition ratio is: 32.0g of Cu, 9.0g of Al, 13.0g of Ni, 36.0g of Fe, 5.0g of composite lubricating phase (Ag2MoO4+Ag) and 5.0g of composite strengthening phase (Ti3SiC2+TiAl); other conditions are consistent with Example 1.
[0100] The performance of the friction-resistant material of comparative example 1 is compared with that of the high temperature friction-resistant material of embodiment 1. The results are shown in Table 1. It can be seen that the hardness, compressive strength and bending strength of the friction-resistant material of comparative example 1 decrease, and the wear rate increases. This is because when Cr and La2O3 are missing, the refinement and dispersion strengthening effects cannot be produced, the hardness and strength of the material decrease, resulting in reduced wear resistance.
[0101] Table 1 Comparison of Comparative Example 1 with Example 1
[0102]
[0103] Comparative Example 2
[0104] Compared with Example 3, Comparative Example 2 provides a friction-resistant material, in which the composite lubricating phase (Ag2MoO4+Ag) in Example 3 is replaced by graphite as the lubricating phase; other material conditions are consistent with those in Example 3.
[0105] The performance of the friction-resistant material of Comparative Example 2 is compared with the performance of the high-temperature friction-resistant material of Example 3. The results are shown in Table 2. It can be seen that at 600°C, the friction coefficient of the friction-resistant material of Comparative Example 2 increases and the wear rate increases. This is because Ag2MoO4 and Ag have excellent lubrication properties in a high-temperature environment, while graphite has relatively poor lubrication ability in a high-temperature environment, resulting in an increase in the friction coefficient of the friction-resistant material of Comparative Example 2 and an increase in wear.
[0106] Table 2 Comparison of Comparative Example 2 with Example 3
[0107]
[0108] Comparative Example 3
[0109] Compared with Example 3, Comparative Example 3 provides a friction-resistant material, in which the composite strengthening phase (Ti3SiC2+TiAl) in Example 3 is replaced by Al2O3 as the strengthening phase; other conditions are consistent with Example 3.
[0110] The performance of the friction-resistant material of Comparative Example 3 is compared with that of the high-temperature friction-resistant material of Example 3. The results are shown in Table 3. It can be seen that the compressive strength and bending strength of the friction-resistant material prepared in Comparative Example 3 are reduced, and the wear rate is increased. This is because the interface bonding force between Al2O3 and the copper-iron alloy is lower than the interface bonding force between (Ti3SiC2+TiAl) and the copper-iron alloy, resulting in a decrease in material strength, and the material is more likely to peel off from the surface during the friction process, so the wear resistance is reduced.
[0111] Table 3 Comparison of Comparative Example 3 with Example 3
[0112]
[0113] Comparative Example 4
[0114] Comparative Example 4 provides a friction-resistant material, whose composition ratio is: 41.0g of Cu, 10.0g of Al, 14.0g of Ni, 12.0g of Fe, 2.0g of Cr, 2.0g of La2O3, 2.0g of composite lubricating phase (Ag2MoO4+Ag) and 17.0g of composite strengthening phase (Ti3SiC2+TiAl); other conditions are consistent with Example 2.
[0115] The performance of the friction-resistant material of comparative example 4 is compared with the performance of the high temperature friction-resistant material of embodiment 2. The results are shown in Table 4. It can be seen that the hardness, compressive strength and flexural strength of the friction-resistant material of comparative example 4 decrease, and the friction coefficient and wear rate increase. The main reasons are: the reduction of Fe content in the copper-iron alloy matrix is lower than the range specified in the present invention; the content of the composite lubricating phase (Ag2MoO4+Ag) decreases, which is lower than the range specified in the present invention; the content of other alloy elements and strengthening phases increases, which is higher than the range specified in the present invention; this causes the phase composition of the alloy material to change, the impurity elements to increase, and the internal interface bonding force of the material to decrease, so the hardness, compressive strength and flexural strength decrease, and the wear rate increases; at the same time, the content of the composite strengthening phase (Ti3SiC2+TiAl) is too much, and the content of the composite lubricating phase (Ag2MoO4+Ag) is too little, which makes it difficult for the friction material to form a stable lubricating film on the surface during friction and wear, so the friction coefficient and wear rate increase.
[0116] Table 4 Comparison of Comparative Example 4 with Example 2
[0117]
[0118] Comparative Example 5
[0119] Compared with Example 3, Comparative Example 5 provides a friction-resistant material, in which the composite lubricating phase (Ag2MoO4+Ag) in Example 3 is replaced by Ag2MoO4; other conditions are consistent with Example 3.
[0120] The performance of the friction-resistant material of Comparative Example 5 is compared with that of the high-temperature friction-resistant material of Example 3. The results are shown in Table 5. It can be seen that the compressive strength and bending strength of the friction-resistant material of Comparative Example 5 are reduced. This is because the interface bonding force between Ag2MoO4 and the copper-iron alloy is lower than that between Ag and the copper-iron alloy. When the content of Ag2MoO4 is too much, cracks are likely to initiate and expand at the grain boundaries of the material, resulting in a decrease in strength.
[0121] Table 5 Comparison of Comparative Example 5 with Example 3
[0122]
[0123] Comparative Example 6
[0124] Compared with Example 3, Comparative Example 6 provides a friction-resistant material, in which the composite lubricating phase (Ag2MoO4+Ag) in Example 3 is replaced by Ag as the lubricating phase; other conditions are consistent with Example 3.
[0125] The performance of the friction-resistant material of Comparative Example 6 is compared with that of the high-temperature friction-resistant material of Example 3. The results are shown in Table 6. It can be seen that at 600°C, the friction coefficient and wear rate of the friction-resistant material of Comparative Example 6 increase. This is because the lubricating effect of Ag is weaker than that of Ag2MoO4 under high temperature environment. When the material does not contain Ag2MoO4, the lubricating ability at high temperature decreases, resulting in an increase in the friction coefficient and aggravated wear.
[0126] Table 6 Comparison of Comparative Example 6 with Example 3
[0127]
[0128] Comparative Example 7
[0129] Compared with Example 2, Comparative Example 7 provides a friction-resistant material, in which the composite strengthening phase (Ti3SiC2+TiAl) in Example 2 is replaced by Ti3SiC2 as the composite strengthening phase; other conditions are consistent with Example 2.
[0130] The performance of the friction-resistant material of Comparative Example 7 is compared with that of the high-temperature friction-resistant material of Example 2. The results are shown in Table 7. It can be seen that the compressive strength and bending strength of the friction-resistant material of Comparative Example 7 are reduced. This is because the interface bonding force between Ti3SiC2 and the copper-iron alloy is lower than that between TiAl and the copper-iron alloy. When the content of Ti3SiC2 is too much, cracks are likely to initiate and expand at the grain boundaries of the material, resulting in a decrease in strength.
[0131] Table 7 Comparative Example 7 compared with Example 2
[0132]
[0133] Comparative Example 8
[0134] Compared with Example 2, Comparative Example 8 provides a friction-resistant material, in which the composite reinforcement phase (Ti3SiC2+TiAl) in Example 2 is replaced by TiAl as the reinforcement phase; other conditions are consistent with Example 2.
[0135] The performance of the friction-resistant material of Comparative Example 8 is compared with the high-temperature friction-resistant material of Example 2. The results are shown in Table 8. It can be seen that the wear rate of the friction-resistant material of Comparative Example 8 increases. This is because Ti3SiC2 can reduce the plowing and peeling effects of the contact surface through the pinning mechanism during the wear process, and the high-temperature oxidation product of Ti3SiC2 can play an effective anti-wear and friction-reducing role, so the lack of Ti3SiC2 in the material leads to an increase in the wear rate.
[0136] Table 8 Comparative Example 8 compared with Example 2
[0137]
[0138] Comparative Example 9
[0139] Compared with Example 3, Comparative Example 9 provides a friction-resistant material, wherein the ball milling process of the composite lubricating phase (Ag2MoO4+Ag) powder is:
[0140] Dry ball milling was carried out under argon protective atmosphere, with a ball-to-material ratio of 1:1 and a rotation speed of 100 r / min. The milling was stopped every 15 minutes and continued after 2 minutes of stopping. The ball milling time was 8 hours.
[0141] The ball milling process of the composite strengthening phase (Ti3SiC2+TiAl) powder is the same as that of the composite lubricating phase (Ag2MoO4+Ag);
[0142] Other conditions are consistent with those in Example 3.
[0143] The performance of the friction-resistant material of Comparative Example 9 is compared with that of the high-temperature friction-resistant material of Example 3. The results are shown in Table 9. It can be seen that the strength of the friction-resistant material of Comparative Example 9 decreases and the wear rate increases. This is because Comparative Example 9 did not perform high-energy ball milling when preparing the composite lubricating phase (Ag2MoO4+Ag) powder and the composite reinforcing phase (Ti3SiC2+TiAl) powder, resulting in low dispersion and surface chemical energy of the composite lubricating phase (Ag2MoO4+Ag) powder and the composite reinforcing phase (Ti3SiC2+TiAl) powder, and the bonding strength with the matrix decreased after adding the copper-iron alloy matrix.
[0144] Table 9 Comparative Example 9 compared with Example 3
[0145]
[0146] Comparative Example 10
[0147] Compared with Example 1, Comparative Example 10 provides a friction-resistant material, wherein the hot pressing sintering process is as follows: a copper-iron alloy matrix raw material, a composite lubricating phase (Ag2MoO4+Ag) powder and a composite strengthening phase (Ti3SiC2+TiAl) powder are mixed by dry ball milling to obtain a mixed powder, which is loaded into a graphite mold and placed in a spark plasma sintering furnace for hot pressing sintering, and the vacuum degree is less than 1×10 -1 Pa, the heating rate is 100°C / min, the sintering temperature is 920°C, the applied pressure is 30MPa, the constant temperature and pressure are maintained for 5min, the hot pressing sintering is terminated, and the furnace is cooled to room temperature; other conditions are consistent with Example 1.
[0148] The performance of the friction-resistant material of Comparative Example 10 is compared with that of the high-temperature-resistant friction material of Example 1. The results are shown in Table 10. It can be seen that the hardness and strength of the friction-resistant material of Comparative Example 10 decrease, and the wear rate increases. This is because the sintering temperature in Comparative Example 10 is too high, higher than the range specified in the present invention, resulting in component segregation of the copper-iron alloy matrix, and the sintering pressure is too low, lower than the range specified in the present invention, resulting in a decrease in the hardness and strength of the material.
[0149] Table 10 Comparative Example 10 compared with Example 1
[0150]
Claims
1. A composite modified high temperature resistant friction material, characterized in that: Taking the total mass of the high temperature resistant friction material raw material as 100%, the components and their mass fractions are as follows: Copper-iron alloy matrix 70.0% to 90.0%, composite lubricating phase 5.0% to 15.0%, composite strengthening phase 5.0% to 15.0%; The raw material of the copper-iron alloy matrix is a mixed powder composed of copper, aluminum, nickel, iron, chromium and lanthanum trioxide. Taking the total mass of the raw material of the high-temperature friction material as 100%, the components and their mass fractions of the raw material of the copper-iron alloy matrix are as follows: Copper 30.0%~45.0%, aluminum 3.0%~9.0%, nickel 3.0%~13.0%, iron 19.5%~36.0%, chromium 0.5%~1.0%, lanthanum trioxide 0.5%~1.0%; The composite lubricating phase is a mixed powder made by mixing Ag2MoO4 and Ag by wet ball milling. Taking the total mass of the composite lubricating phase raw material as 100%, the components and their mass fractions are: Ag2MoO4 30.0% to 70.0%, Ag 30.0% to 70.0%; The composite strengthening phase is a mixed powder formed by mixing Ti3SiC2 and TiAl by wet ball milling. Taking the total mass of the composite strengthening phase raw material as 100%, the components and their mass fractions are: Ti3SiC2 60.0% to 80.0%, TiAl 20.0% to 40.0%; The preparation method of the high temperature resistant friction material is as follows: a copper-iron alloy matrix raw material, a composite lubricating phase and a composite reinforcing phase are mixed by mechanical ball milling to obtain a mixed powder, and the mixed powder is hot pressed and sintered to prepare the material; the steps of hot pressing and sintering are as follows: The mixed powder prepared by ball milling was placed into a mold and placed in a spark plasma sintering furnace for hot pressing and sintering with a vacuum degree of less than 1×10 -1 Pa, the heating rate is 100℃ / min~150℃ / min, the sintering temperature is 850℃~900℃, the applied pressure is 35MPa~40MPa, the constant temperature and pressure are maintained for 5min~10min to end the hot pressing sintering, and the furnace is cooled to room temperature.
2. The composite modified high temperature resistant friction material according to claim 1, characterized in that: In the composite lubricating phase, Ag2MoO4 is a powder having a particle size greater than or equal to 200 mesh, and Ag is a powder having a particle size greater than or equal to 200 mesh; In the composite strengthening phase, Ti3SiC2 is a powder having a particle size greater than or equal to 200 meshes, and TiAl is a powder having a particle size greater than or equal to 200 meshes.
3. A composite modified high temperature resistant friction material according to claim 1 or 2, characterized in that: The composite lubricating phase is prepared according to the following method: Ag2MoO4 powder and Ag powder are wet ball-milled under inert gas protection. The ball-milling medium is ethanol, the ball-to-material ratio is 3:1-4:1, the rotation speed is 250r / min-350r / min, the ball-milling time is 8h-12h, and the ball-milling is stopped every 5min-10min. After stopping for 2min-3min, the ball-milling is continued to prepare a mixed powder, which is a composite lubricating phase.
4. A composite modified high temperature resistant friction material according to claim 1 or 2, characterized in that: The composite reinforcement phase is prepared according to the following method: Ti3SiC2 powder and TiAl powder are wet ball-milled under inert gas protection. The ball-milling medium is ethanol, the ball-to-material ratio is 3:1-4:1, the rotation speed is 250r / min-350r / min, the ball-milling time is 8h-12h, and the ball-milling is stopped every 5min-10min. After stopping for 2min-3min, the ball-milling is continued to prepare a mixed powder as a composite reinforcement phase.
5. The composite modified high temperature resistant friction material according to claim 1, characterized in that: The steps of mechanical ball milling are as follows: The copper-iron alloy matrix raw material, the composite lubricating phase and the composite strengthening phase are dry-milled in an inert gas atmosphere, with a ball-to-material ratio of 1:1 to 2:1, a rotation speed of 100 r / min to 150 r / min, a ball milling time of 8 h to 10 h, and the ball milling is stopped every 10 min to 15 min, and the ball milling is continued after stopping for 1 min to 2 min; a mixed powder is prepared; the grinding jar and the grinding balls used in the ball milling are made of tungsten carbide cemented carbide.
Citation Information
Patent Citations
A self-lubricating copper-Ti3SiC2-NbSe2 composite material and its preparation method
CN102703161B
Brake block friction material taking Mn+1XAn lamellar compound as antifriction phase and preparation method
CN103184385A
A kind of iron-copper based powder metallurgy anti-friction material and preparation method thereof
CN104384503B
A copper-iron-based braking composite material and its preparation method
CN106086585B
A friction material, a brake pad including the friction material, and a method for preparing the brake pad.
CN110284083B